Art-technologies for creating an artistic image: issues of imitation and the transitivity of the creative process - Sovhyra, Tetiana (Creativity Studies, 2025)
The article reveals certain aesthetic patterns in the creation of augmented reality content, namely the importance of modelling the real environment, transitivity, and simulation of traditional practices of creating sculptural forms. These issues are analyzed on the author’s projects examples organized through the augmented reality use (applications REMS Companion App and MININ Art). An aesthetic patterns interdisciplinary research of augmented reality content perception allows us to draw significant conclusions about the artistic uniqueness of virtual images. The article reveals certain regularities in the creation of augmented reality content, including the peculiarities of imitation of traditional sculptural techniques and materials texture. It has been established that in order to create a realistic embodiment of virtual models in a real environment and to make these objects three-dimensional, it is important to take into account the peculiarities of chiaroscuro. Technologically, this can be done by installing a light source in the virtual scene that will illuminate objects at a certain angle. Consideration of the results of technological experience of content generation suggests that augmented reality allows the artist to create a transitional creative environment by imitating real space. When virtual content is detached from its marker (the image of real space), the specific author’s context is lost. As a result, we can safely talk about the content uniqueness created with the help of augmented reality technology. Having all the signs of artistic creativity, these models can be called augmented reality sculptures – a form of synthetic digital and visual art.